Improving Street Children Welfare with Self Esteem Theory - Pipin Armita (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
This study was intended to provide a solution to community or social organizations how to improve social welfare of street children with the self esteem theory and to know what are the constraints faced by street children in improving social welfare. Acceptance and knowing the existing potential toward street chlidren are the basic concept of enhancing street children social welfare, because street children are still able to develop themselves optimally. This article offers four aspects in providing solutions to improve social welfare of street children with self esteem theory: power, significance, virtue, and competence. The basic concept is to offer treatment, protection, and empowerment of street children that can give a better results. All they take then is the willingness of all parties, especially social worker, community, and social organizations to sit together, discuss to find the best solution for street children and then formulate an intervention program that targeted and simultaneously undertake a more coordinated division of work. The basic argument that can be worked out is the street children can develop themselves if a community or social institution introduced self esteem theory in them.